In-situ flanged intrascleral fixation of dislocated foldable intraocular lens - Ayman M.A Elsayed; Ahmed Samir; Ayman Lotfy (Delta Journal of Ophthalmology, 2023)
Purpose The aim of this study was to investigate the efficacy of in-situ transconjunctival scleral fixation of dislocated one-piece foldable intraocular lens (IOL) with flanged prolene 6/0 suture. Patients and methods The study included seven eyes of seven patients with dislocated IOL. A 6/0 prolene suture was threaded into a 30-G needle that was then passed transconjunctively. The needle was passed through the optic–haptic junction of the luxated IOL. The prolene was then retrieved through the corneal tunnel. Two central and two scleral bulbs (flanges) were created by heating the ends of the prolene suture. Results The best-corrected visual acuity was significantly improved from 0.16±0.05 preoperatively to 0.62±0.08 3 months postoperatively (P=0.006). There were nonsignificant IOP elevation and endothelial cell loss (P>0.05). All cases had well-centered IOL. No postoperative complications such as vitreous hemorrhage, macular edema, retinal detachment, or endophthalmitis were recorded. Conclusion In-situ transconjunctival scleral fixation of foldable one-piece IOLs is a safe effective technique for fixing dislocated IOLs.